A Facile Synthesis of LaFeO3‐Based Perovskites and Their Application towards Sensing of Neurotransmitters. Issue 20 (11th July 2017) - Vijayaraghavan, Thiruvenkadam; Sivasubramanian, Ramanathan; Hussain, Shamima; Ashok, Anuradha
Abstract: Lanthanum ferrite (LaFeO3 ) was prepared from its oxide precursors using solid state synthesis technique. Structural analysis indicate that the synthesized perovskite is phase pure having orthorhombic crystal structure with space group Pnma (62) and cell dimensions a=5.5392 Å, b=7.8573 Å, c=5.5584 Å. Morphological studies show aggregated spherical shaped nanoparticles having orthorhombic crystal structure with an average particle size of ∼ 50 nm. The LaFeO3 modified glassy carbon electrode (GCE) was studied to determine its electrocatalytic activity towards dopamine oxidation. It is seen that the LaFeO3 /GCE showed excellent electrocatalytic activity with a manifold increase in oxidation current compared to bare GCE. The sensing was carried out using Differential Pulse Voltammetry (DPV) wherefrom a detection limit of 10 nM and two linear regimes from 10 μM to 100 μM and 120 μM to 180 μM was deduced. The influence of ascorbic acid and uric acid in the sensing of dopamine was investigated. The estimation of dopamine in human blood samples were analyzed with excellent recovery values. Abstract : LaFeO3 nanoparticles was synthesized by a solid state synthesis technique and their efficacy towards dopamine detection was studied. The nanoparticles showed enhanced catalytic activity towards dopamine with a detection limit of 10 nM. The sensor showed good reproducibility and stability.